Comparison of Risk Factors & Angiographic Profiles between Young Patients with ST Segment Elevation Myocardial Infarction and Non-ST Segment Elevation Myocardial Infarction (Bangladesh Heart Journal, 2021)
Background: Coronary artery disease is the leading cause of death in the world. Advancing age is a well-recognized risk factor for acute myocardial infarction (AMI). Myocardial infarction is less common in young adults. Prevalence of acute coronary syndrome in young individuals is increasing progressively. These patients have different risk profile, presentation and prognosis. Early recognition and risk factor modification in this population sub-set is of key importance.Objectives: The purpose of the present study was to determine the differences in risk factors and coronary angiographic profile of young patients with ST-segment elevated myocardial infarction (STEMI) vs. those with non-ST-segment elevated myocardial infarction (NSTEMI). Methods: In this cross sectional analytical study total 135 patients (70 STEMI and 65 NSTEMI) aged ≤45 years were enrolled to see the differences of risk factors and angiographic profile.Results: The mean age of the study population was 39.39±5.12 years and the study showed male predominance (90.40 % was male and 9.60 % was female). Smoking/tobacco consumption was significantly higher in STEMI patients, whereas diabetes mellitus and hypertension were more prevalent in NSTEMI patients. The frequency of single vessel disease and involvement of left anterior descending artery was significantly higher in young STEMI patients. In case of young NSTEMI patients frequency of triple vessel disease, noncritical coronary artery disease and involvement of left circumflex coronary was significantly higher. The frequency of double vessel disease and involvement of left main coronary artery was also nonsignificantly higher in young NSTEMI patients. There was no significant difference regarding involvement of right coronary artery.Conclusion: There are significant differences between young STEMI and young NSTEMI patients in respect to risk factors and angiographic profile. Key words: Young patient, STEMI, NSTEMI, Risk factors, Coronary angiographic profile.Bangladesh Heart Journal 2021; 36(2): 124-132